Ecclesiastical Support to the Master of Avis: An Analysis from the Aclamation Act of 1385 - Coelho, André Madruga (2017)
The death of king Fernando of Portugal in October 1383 without male heirs opened a succesion crisis. Despite the studies that have been made concerning the composition of the factions that supported the various pretenders to the throne, in special about the participation of town elites and nobility, there are still few contributions on the participation of the clergy in the conflict. This is a matter of great importance, given the religious character of the royal power in the legitimation of kings and dynasties, in particular in a period marked by the Schism of the Catholic Church. Therefore, starting from the list of signatories and witnesses of the acclamation act of João I, made in the cortes of Coimbra in 1385, our aim is to analyse the participation of the clergy in the fight for the throne, identifying the main protagonists of each party and the reasons for their positions, as well as the consequences for their later ecclesiastic and political careers.